IR780-Based Nanotheranostics and In Vivo Effects: A Review - Márcia Célia Pacheco Fialho; Maria Alice de Oliveira; Marina Guimarães Carvalho Machado; Carlos Marchiorio Lacerda; Vanessa Carla Furtado Mosqueira (Journal of Nanotheranostics)
Photodynamic and photothermal therapies with IR780 have gained exponential interest, and their photophysical properties have demonstrated promise for use in antitumor and antimicrobial chemotherapy. IR780 and its derivatives are valuable in labeling nanostructures with different chemical compositions for in vitro and in vivo fluorescence monitoring studies in the near-infrared (NIR) spectrum. The current literature is abundant on this topic, particularly with applications in the treatment of different types of cancer using laser illumination to produce photodynamic (PDT), photothermal (PTT), and, more recently, sonodynamic therapy (SDT) approaches for cell death. This review aims to update the state of the art concerning IR780 photosensitizer as a theranostic agent for PDT, PTT, SDT, and photoacoustic (PA) effects, and fluorescence imaging monitoring associated with different types of nanocarriers. The literature update concerns a period from 2017 to 2024, considering, more specifically, the in vivo effects found in preclinical experiments. Some aspects of the labeling stability of nanostructured systems will be discussed based on the evidence of IR780 leakage from the nanocarrier and its consequences for the reliable analysis of biological data.